2021
DOI: 10.1007/s11096-021-01296-1
|View full text |Cite
|
Sign up to set email alerts
|

A theoretically informed, mixed-methods study of pharmacists’ aspirations and readiness to implement pharmacist prescribing

Abstract: Background Studies have highlighted advancing clinical pharmacy practice in Qatar. Objective To explore pharmacists’ aspirations and readiness to implement pharmacist prescribing. Setting Hamad Medical Corporation (HMC), the main provider of secondary and tertiary care. Method A sequential explanatory mixed-methods design. Questionnaire items were derived from the Consolidated Framework of Implementation Research (CFIR), in domains of: awareness/support; readiness; implementation; and facilitators and barriers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…5 In Saudi Arabia, pharmacy practice is advancing quickly, and through collaborative practice agreements, pharmacists have prescribing privileges that can be used in cases of emergency. 14,15 Our study showed that pharmacists have specific roles during emergencies. All hospitals reported that pharmacists are responsible for the three following roles: maintain effective distribution and control, collaborate on medication management, and develop and maintain first-aid skills.…”
Section: Discussionmentioning
confidence: 78%
“…5 In Saudi Arabia, pharmacy practice is advancing quickly, and through collaborative practice agreements, pharmacists have prescribing privileges that can be used in cases of emergency. 14,15 Our study showed that pharmacists have specific roles during emergencies. All hospitals reported that pharmacists are responsible for the three following roles: maintain effective distribution and control, collaborate on medication management, and develop and maintain first-aid skills.…”
Section: Discussionmentioning
confidence: 78%
“…Internationally, it is common for healthcare professions to have structured support frameworks for support of practice-based learning [ 9 , 10 ] and in the UK there are developing supervision models for advanced pharmacy practice [ 11 ]. This need for consideration of structures and processes within the organisational environment has also been shown in other countries [ 12 , 13 ] and has relevance in primary and secondary care.…”
Section: Introductionmentioning
confidence: 78%
“…The pharmacists have expressed that they were largely aspired to, and ready to be prescribers. 17 In 2020, a cross-sectional survey study was conducted on hospital pharmacists in Saudi Arabia about views, prescribing legislation and barriers to implementing pharmacist prescribing.…”
Section: Resultsmentioning
confidence: 99%